PENGARUH ETIKA AUDITOR, PENGALAMAN AUDITOR, DAN GENDER TERHADAP KEMAMPUAN MENDETEKSI PRAKTIK AKUNTANSI KREATIF (Studi pada BPK RI Perwakilan Sumatera Selatan dan KAP di Sumatera Bagian Selatan) - Anggi Monita Sari (AKUNTABILITAS, 2014)
This research aimed at investigating the effect of auditor ethics (independence, integrity, and objectivity), experience, and gender on the ability to detect creative accounting practices (at BPK RI Representative South Sumatra and KAP (Public Accounting Firms) Southern Sumatra). The research was conducted at BPK RI Representative South Sumatra and KAP Southern Sumatra with 129 respondents, 97 of whom were analyzed. Data were analyzed using multiple regression model. Results show that auditor ethics (independence, integrity, and objectivity), experience, and gender simultaneously affect the ability to detect creative accounting practices with (adjusted R square of 32%), while auditor’s independence, integrity, and experience have partial effect. However, objectivity and gender does not have significant effect on detecting creative accounting practices.